2022
DOI: 10.1186/s43093-022-00122-y
|View full text |Cite
|
Sign up to set email alerts
|

The consequence of the credit risk on the financial performance in light of COVID-19: Evidence from Islamic versus conventional banks across MEA region

Abstract: Purpose The increased number of nonperforming loans (NPLs) during COVID-19 pandemic has interrogated the robustness of banks and stability of the whole banking segment. We examine the impact of credit risk (CR) on financial performance (FP) by comparing Islamic banks (IBs) to conventional banks (CBs). We also investigate the influence of COVID-19 on this association. Design/methodology/approach Our sample includes the largest 200 banks across 15 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 82 publications
(90 reference statements)
3
16
0
Order By: Relevance
“…The financial institutions reduced the request or acceptance of immovable collateral during the COVID-19 era because of the likelihood of an increase in the number of defaults due to decreased productivity of farmers that will enable the repayment. Despite the legal force associated with immovable collateral, this kind of collateral has some risks associated with taking possession of the collateral due to the owner's social or political influence (Ahmed et al ., 2022). The moveable collateral can be easily converted to liquid cash in default.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The financial institutions reduced the request or acceptance of immovable collateral during the COVID-19 era because of the likelihood of an increase in the number of defaults due to decreased productivity of farmers that will enable the repayment. Despite the legal force associated with immovable collateral, this kind of collateral has some risks associated with taking possession of the collateral due to the owner's social or political influence (Ahmed et al ., 2022). The moveable collateral can be easily converted to liquid cash in default.…”
Section: Resultsmentioning
confidence: 99%
“…Given the recent financial turbulence in the overall economy occasioned by the COVID-19 pandemic, it is not difficult to see the importance of managing credit risks. Credit risk management means increasing the likelihood of success, reducing the possibility of failure, limiting the uncertainty of overall financial performance and preventing an institution from suffering an unacceptable loss in the hands of borrowers (Ahmed et al ., 2022). The overall effect of risk factors on credit delivery to farmers is high loan delinquency, which results from poor production and productivity.…”
Section: Introductionmentioning
confidence: 99%
“…However, lending growth relies on financial liberalization and banking reforms, which at some point is negatively affected by the selection of subprime customers that gives rise to weaker asset quality (Aysan & Ozturk, 2018 ). Similarly, the higher non-performing assets (herein after NPA) negatively affect bank’s profitability (Epure & Lafuente, 2015 ; Das & Uppal, 2021 ; Hunjra et al, 2020 ; Musneh et al, 2021 ; Ahmed et al, 2022 ), which enhances the financing cost, and reduces the supply of future credits (Aiyar et al, 2015 ). The private sector predicts the future credit default of banking companies and uses it as a driving force to make decisions and gain confidence in expanding or contracting their credit exposure in future (Bordalo et al, 2018 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The ROA is determined by asset quality which is impacted by the percentage of (NPA) non-performing assets (Das & Ghosh, 2007). The ratio of NPA to total assets, capital requirement as the proxy of credit risk (Bayyoud & Sayyad, 2015), and ROE as the measure of a bank's performance (Ahmed et al, 2022) was used in a study that concluded that capital requirement has a positive impact on bank's performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Risk can be defined as the probability of default, loss, damage, or threat caused by external and internal factors (Gabriel et al, 2022;Inegbedion et al, 2020). This risk may cause the problem of bank failure (Ahmed et al, 2022).…”
Section: Introductionmentioning
confidence: 99%